IMS application developer's handbook - Olsson, Ulf.; Mulligan, Catherine; Fikouras, Ioannis; Ryde, Anders; Stille, Mats.; Noldus, Rogier (Amsterdam ; Boston : Academic Press, 2011)
IMS Application Developer Handbook will give a hands-on view of exactly what needs to be done by IMS application developers to write an application and take it "live" on an operator's network. It will offer practical guidance on building innovative applications using the features and capabilities of the IMS network, show how the rapidly changing development environment is impacting on the business models employed in the industry and how existing network solutions can be moved towards IMS. The book will also elaborate on how IMS applies basic VoIP principles and techniques to realise a true multi-access, multimedia network. The Handbook demonstrates how the IMS architecture and protocols are applied to multimedia services from a "hands-on" perspective, ensuring that developers know how to use the IMS most effectively for their chosen application. Clear, concise and comprehensive view of the IMS and Rich Communication Suite (RCS) for developers. Written by established experts in the IMS services layer, who have been involved in many customer projects for the implementation of fixed mobile converged IMS network and service. Covers potential service and operator scenarios for the IMS architecture; it is significantly more than merely a description of the IMS standards.
Keywords: Internet Protocol multimedia subsystem; Internet Protocol multimedia subsystem